Get the IT job of your dreams. (Manning Publications, 2023)
Do you dream of getting a job in Information Technology (IT) but don't know where to start? Perhaps you want to make a career change, but you're struggling to find information and guidance about the field and all the components you'll need to learn. Or you've heard IT is a great field, but you don't know all the different types of jobs--and which one is right for you. In this course you will learn about all the types of jobs in the IT fields and which job is right for you based on your background, knowledge, education and preferences. We cover the software, hardware, procedures, and concerns that IT professionals address. By the end of this course, you'll be informed and confident enough to choose the job of your dreams, and to start pursuing your new career.